2011
DOI: 10.1186/1471-2466-11-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term (5 year) safety of bronchial thermoplasty: Asthma Intervention Research (AIR) trial

Abstract: BackgroundBronchial thermoplasty (BT) is a bronchoscopic procedure that improves asthma control by reducing excess airway smooth muscle. Treated patients have been followed out to 5 years to evaluate long-term safety of this procedure.MethodsPatients enrolled in the Asthma Intervention Research Trial were on inhaled corticosteroids ≥200 μg beclomethasone or equivalent + long-acting-beta2-agonists and demonstrated worsening of asthma on long-acting-β2-agonist withdrawal. Following initial evaluation at 1 year, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(125 citation statements)
references
References 16 publications
1
111
0
9
Order By: Relevance
“…The clinical effectiveness of BT has been confirmed in two prospective cohort feasibility studies, [14,22] three randomised controlled trials (RCTs), [23][24][25] one of which was published in the New England Journal of Medicine, and three prospective cohort followup studies interrogating long-term outcomes and safety [26][27][28] (the relevant studies are summarised in Table 1). The AIR trial enrolled 112 patients with moderate to severe asthma (FEV 1 60 -85% of predicted).…”
Section: What Is the Impact Of Bt On Patient Related Outcomes?mentioning
confidence: 92%
See 1 more Smart Citation
“…The clinical effectiveness of BT has been confirmed in two prospective cohort feasibility studies, [14,22] three randomised controlled trials (RCTs), [23][24][25] one of which was published in the New England Journal of Medicine, and three prospective cohort followup studies interrogating long-term outcomes and safety [26][27][28] (the relevant studies are summarised in Table 1). The AIR trial enrolled 112 patients with moderate to severe asthma (FEV 1 60 -85% of predicted).…”
Section: What Is the Impact Of Bt On Patient Related Outcomes?mentioning
confidence: 92%
“…The long-term safety of BT (up to 5 years) has been demonstrated in three studies. [26][27][28] There is no consistent evidence that BT is causally associated with bronchial stenosis or bronchiectasis. In the AIR2 follow-up study, only three of 93 patients developed new (n=1) or worsening bronchiectasis (n=2) as shown on HRCT; it remains unclear whether this was a complication of asthma or related to BT.…”
Section: What Adverse Events Are Associated With Bt?mentioning
confidence: 99%
“…Other studies did not confirm these results but showed a decrease in the rate of asthma exacerbations and hospitalisations [100]. No clinical complications were observed in the long run, and pulmonary function remained stable over a period of 5 years [101]. Therefore, this approach might be a reasonable option for patients not responding to current treatment.…”
Section: Nonpharmacological ''Targeted'' Treatmentmentioning
confidence: 95%
“…There was no deterioration in lung function for 5 years after BT, making the conclusion that it is safe for 5 years in severe asthma patients. In another follow-up study, 45 of 52 treated and 24 of 49 control group subjects who participated in AIR1 trial were selected for long-term follow-up of 5 years and 3 years, respectively (25). The rate of respiratory adverse events in the BT group (AEs/subject) remained stable in years 2-5 following BT.…”
Section: Long-term Study Human Studiesmentioning
confidence: 99%